Non-alcoholic fatty liver disease: What the clinician needs to know - Machado, Mariana Verdelho (World journal of gastroenterology : WJG, 2014)
Non-alcoholic fatty liver disease(NAFLD) is the most frequent cause of liver disease in the Western world. Furthermore, it is increasing worldwide, paralleling the obesity pandemic. Though highly frequent, only about one fifth of affected subjects are at risk of developing the progressive form of the disease, non-alcoholic steatohepatitis with fibrosis. Even in the latter, liver disease is slowly progressive, though, since it is so prevalent, it is already the third cause of liver transplantation in the United States, and it is predicted to get to the top of the ranking in few years. Of relevance, fatty liver is also associated with increased overall mortality and particularly increased cardiovascular mortality. The literature and amount of published papers on NAFLD is increasing as fast as its prevalence, which makes it difficult to keep updated in this topic. This review aims to summarize the latest knowledge on NAFLD, in order to help clinicians understanding its pathogenesis and advances on diagnosis and treatment.